Assessment of age‐related differences in smoking status and health‐related quality of life (HRQoL): Findings from the 2016 Behavioral Risk Factor Surveillance System. Issue 1 (10th July 2018) - Dube, Shanta R.; Liu, Jin; Fan, Amy Z.; Meltzer, Martin I.; Thompson, William W.
Abstract: Despite significant declines in the use of cigarettes, a significant proportion of adults smoke. This study explores the association between smoking and health‐related quality of life (HRQoL) by age. The 2016 Behavioral Risk Factor Surveillance System survey was administered to adults in 50 states and District of Columbia (n = 437, 195). Physically unhealthy days (PUDs) and mentally unhealthy days (MUDs)) were regressed on age strata (18–24, 25–34, 35–44, 45–54, 55–64, ≥ 65 years) and smoking status (never, former, someday, and everyday) using negative binomial regression models with adjustment for sociodemographic covariates. For each age group, everyday smoking highly predicted PUDs and MUDs. Predicted PUDs increased with age; predicted MUDs decreased with age. Among adults aged 45–54 and 55–64 years, 3‐day difference in PUDs was observed between never smokers and everyday smokers. Among young adults (18–24 years), a 4.3‐day difference in MUDs was observed between everyday and never smokers. The discrepancies were nonlinear with age. The observed relationship between smoking and HRQoL provides novel information about the need to consider age when designing community‐based interventions. Additional research can provide needed depth to understanding the relationship between smoking and HRQoL in specific age groups.